Vitamin A and Hydrochlorothiazide Causing Severe Hypercalcemia in a Patient With Primary Hyperparathyroidism - Ron T. Varghese MBBS; Khaled Khasawneh MD; Raman K. Desikan MD; Anandaraj Subramaniam MBBS; Todd Weaver PharmD; Ganesh K. V. Nair MD (SAGE Publishing, 2019)
Objective . To report a case of severe hypercalcemia, exacerbated by vitamin A supplementation and hydrochlorothiazide, in a patient with primary hyperparathyroidism. Methods . Clinical and laboratory findings are presented along with response to therapy. Results . A 68-year-old white female presented to the emergency department complaining of nausea, vomiting, and altered mental status. Laboratory findings revealed calcium 15.8 mg/dL (8.4-10.2), albumin 4.1 g/dL (3.8-4.8), and parathyroid hormone 62 pg/mL (14-64). Serum calcium improved after intravenous hydration with normal saline. Prior to this hospitalization, over-the-counter medications were significant for calcium (600 mg daily), vitamin A (11 000 IU daily), and vitamin D (800 IU daily).The patient's prescription medications were significant for hydrochlorothiazide (12.5 mg daily). Twenty-four-hour urine calcium was subsequently found to be 146 mg (35-250). Myeloma, lymphoma, and sarcoidosis were ruled out as the etiology for hypercalcemia. The diagnosis of primary hyperparathyroidism was confirmed. She was treated surgically for primary hyperparathyroidism. The right and left superior parathyroid showed hypercellular parathyroid on pathology. The patient was normocalcemic after surgery. Conclusion . Previous reports suggest that very high doses of vitamin A is required to cause hypercalcemia. This case suggests that in a setting of primary hyperparathyroidism and hydrochlorothiazide therapy, vitamin A may contribute to the development of severe hypercalcemia in patients who are on calcium and vitamin D supplements. Given their biologic effects, public awareness needs to be created regarding the injudicious use of vitamins.